Perceived recovery-stress states and sleep in pre- and post-menarche elite youth swimmers - Kullik, L.; Kiel, A.; Kellmann, M.; Jakowski, S. (International Journal of Sport and Exercise Psychology, 2026)
The influence of menstruation on athletes represents a current topic of scientific research. Investigations focus not only on performance but also on assessing the effects on regeneration and well-being. To investigate differences in young females, this study examined perceived stress, recovery, and sleep parameters in German youth female elite athletes distinguished by menarche status. The sample includes 20 elite swimmers (M = 12.90 ± 1.68 years) who participated in 20-day psychometric monitoring and wore actigraphy wristbands to evaluate sleep parameters. Mixed effects models were calculated to examine the difference between pre-menarche (n = 11; M = 11.91 ± 1.22 years) and post-menarche (n = 9; M = 14.11 ± 1.36 years) athletes. The results of our study revealed significantly lower ratings of morning Lack of Activation (p < 0.01) and evening Overall Stress (p < 0.05) for the post-menarche athletes, as measured by the SRSS. While a group effect for sleep parameters was not identified, these findings shed light on the potential influence of menarche on stress and recovery in elite female athletes. We recommend that coaches of adolescent female athletes evaluate menarche status to contextualize recovery and stress responses. Furthermore, menstrual cycle education should be offered.